REPEATED OPTIMAL CYTOREDUCTIVE SURGERIES IN COMBINED MODALITY TREATMENT OF OVARIAN CANCER. CASE REPORT - S. V. Molchanov; L. A. Kolomiets; O. V. Shpilyeva (Сибирский онкологический журнал)
To date, the algorithm for the treatment of recurrent ovarian cancer and the criteria for selecting patients for performing secondary cytoreductive surgeries have not been fully developed. Although the role of secondary surgery in recurrent ovarian cancer remains controversial, most retrospective studies showed better survival in patients for whom maximal cytoreduction was achieved. Several studies have developed prognostic models for the feasibility of performing complete secondary cytoreduction. We report a rare case of repeated cytoreductive surgeries in combination with chemotherapy for recurrent ovarian cancer. This clinical case indicates the feasibility of performing repeated cytoreductive surgeries in patients with localized recurrent ovarian cancer undergoing previous optimal cytoreductions and having no ascites.